Potential causal association between aspirin use and the reduced risk of hayfever or allergic rhinitis: a Mendelian randomization study - Li, Li; Zhang, Yuanding; Liu, Xiangliang; Li, Junxin; Yang, Qiuyu; Jiang, Jiajia; Liu, Hong; Fu, Zhongying; Chen, Weilun (Frontiers in Immunology, 2023)
The evidence from observational studies on the association between the use of aspirin and the risk of hayfever or allergic rhinitis is conflicting, with a dearth of high-quality randomized controlled trials.Objective: This study aims to investigate the causal relationship between aspirin use and the risk of hayfever or allergic rhinitis.We conducted a two-sample Mendelian randomization (MR) analysis using the inversevariance weighted (IVW), weighted median, and MR-Egger regression methods. We utilized publicly available summary statistics datasets from genome-wide association studies (GWAS) meta-analyses on aspirin use in individuals of European descent (n = 337,159) as the exposure variable, and a GWAS on doctor-diagnosed hayfever or allergic rhinitis in individuals from the UK Biobank (n = 83,529) as the outcome variable.We identified 7 single nucleotide polymorphisms (SNPs) at genome-wide significance from the GWASs associated with aspirin use as instrumental variables (P<5×10−8; linkage disequilibrium r2 <0.1). The IVW method provided evidence supporting a causal association between aspirin use and reduced risk of hayfever or allergic rhinitis (β = -0.349, SE = 0.1356, P = 0.01008). MR-Egger regression indicated no causal association between aspirin use and hayfever or allergic rhinitis (β = -0.3742, SE = 0.3809, P = 0.371), but the weighted median approach yielded evidence of a causal This is a provisional file, not the final typeset article association (β = -0.4155, SE = 0.1657, P = 0.01216). Cochran's Q test and the funnel plot indicated no evidence of heterogeneity and asymmetry, indicating no directional pleiotropy.The findings of the MR analysis support a potential causal relationship between aspirin use and the reduced risk of hayfever or allergic rhinitis.